Capacity building at mid-programme: an international education development programme in Malawi. Issue 3 (2nd April 2016) - Coryell, Joellen; Sailors, Misty; Nelson, Roxanna; Sehin, Oleksandra
ABSTRACT: This article reports on a case study of a mid-programme capacity building evaluation within a large education aid programme collaboration between non-governmental educational organisations in Malawi and US university literacy faculty. The article outlines the programme context and its formal and informal capacity building inputs. Analyses of data collected on capacity building at the midpoint of the programme are offered. The authors argue that capacity is built along the life of large programmes, and evaluating capacity building development (and understanding its challenges) before the end of the programme can help cross-national teams of administrators and implementers in modifying programme operations.